Wanita & keadilan - Zaleha Kamaruddin (Kuala Lumpur: ANZ Charisma, 1999)
Women's rights and women according to Malaysian laws; collection of papers.
Includes bibliographical references (p. 177-188).
Keywords: Women's rights -- -- Malaysia; Women -- -- Legal status, laws, etc. -- -- Malaysia